(untitled) - McQuilkin, Robertson (Secunderabad, India, 2002)
This book 'is a good introduction to biblical ethics that interacts with current issues...' (Carl E.F. Henry). The author foundationally turns to the Bible for answers to key questions that the study of ethics seeks to answer: What should we do or refrain from doing? What attitudes, behavior and qualities are good, and why they are good? Can we be good without God? What is the highest good, the purpose of human existence? The result is an overview of biblical ethics that not only addresses the life of love and wisdom to be lived out by Christians as virtuous individuals, but also as Christians in community, in society and in a world of God's creation. The book contains two major parts. Part one discuses foundational considerations of love, law, root sins and virtues, and situational ethics. The second part applies the Bible to life, in particulars, relationship with God, the issues of sex, marriage and family, life issues, integrity, Christians and society, and decision making.
Keywords: Ethics in the Bible